Réponses

2013-11-23T23:23:01+01:00
Bonsoir

f(x) = \dfrac{1}{4} x^{2} + x - 3

1) Résoudre f(x) = -3.

f(x) =-3\Longleftrightarrow \dfrac{1}{4} x^{2} + x - 3=-3\\\\\Longleftrightarrow \dfrac{1}{4} x^{2} + x =0\\\\\Longleftrightarrow x(\dfrac{1}{4} x + 1)=0\\\\\Longleftrightarrow x=0\ \ ou\ \ \dfrac{1}{4} x + 1=0\\\\\Longleftrightarrow x=0\ \ ou\ \ \dfrac{1}{4} x =-1\\\\\Longleftrightarrow x=0\ \ ou\ \ x =-4.

2) Résoudre f(x) = -4

On sait que 
(\dfrac{1}{2}x+1)^2=\dfrac{1}{4}x^2+x+1

Donc  nous avons 

f(x) = \dfrac{1}{4} x^{2} + x - 3 \\\\f(x)= \dfrac{1}{4} x^{2} + x +1-4 \\\\f(x)=(\dfrac{1}{2} x+1)^2-4

Par conséquent : 

f(x) = -4\Longleftrightarrow (\dfrac{1}{2} x+1)^2-4=-4\\\\ f(x) = -4\Longleftrightarrow (\dfrac{1}{2} x+1)^2=0\\\\ f(x) = -4\Longleftrightarrow \dfrac{1}{2} x+1=0\\\\ f(x) = -4\Longleftrightarrow \dfrac{1}{2} x=-1\\\\ f(x) = -4\Longleftrightarrow x=-2